Epidemiological Aspects of Neonatal Mortality Due To Intrauterine Infection in Kazakhstan - Marzya MAMYRBAYEVA; Nurbek IGISSINOV; Galina ZHUMAGALIYEVA; Akmanat SHILMANOVA (Tehran University of Medical Sciences, 2015)
Background: In this study, we examined the epidemiological aspects of neonatal mortality due to intrauterine infections with regard to regional characteristics. Methods: Consolidated report of the Ministry of Health and Social Development of the Republic of Kazakhstan on children deceased during their first 28 days of life due to intrauterine infections (P23 - congenital pneumonia, P35-39 - infectious diseases specific to the perinatal period) in the country and its regions for 2010 - 2014 was used in this investigation. Descriptive and analytical methods of medical statistics and epidemiology were used as the main method of this 5-year (2010-2014) retrospective study. Results: Overall, 3,298 neonatal deaths from intrauterine infections were recorded in Kazakhstan during the period of 2010-2014, 1,925 of which were early and 1,373 were late neonatal deaths. The average annual rate of neonatal mortality rate from intrauterine infection in the country amounted to 1.73±0.23‰ (95% CI=1.27-2.19‰), whereas trends during the study period decreased (T=−15.3%). Regional characteristics of neonatal mortality were established. Different levels for cartograms of neonatal mortality from intrauterine infections were defined: low (up to 1.28‰), average (from 1.28‰ to 2.12‰) and high (by 2.12‰ and above). Neonatal mortality in the early and late periods was also analyzed. Conclusion: This is the first epidemiological study of neonatal mortality from intrauterine infection, which contains a detailed space-time evaluation. The results of this investigation can be used to improve the state program to combat infant mortality. Keywords: Neonatal mortality, Intrauterine infections, Trends, Cartograms, Kazakhstan